Terapi Sentuhan Pijat Bayi Untuk Merangsang Perkembangan Dan Pertumbuhan Bayi Di Kelurahan Katimbang Kecamatan Biringkanaya - Leli, Leli; Arda, Darmi; Fatimah, Sitti; Juniarti, Rizky Auliah; Jariyah, Ainun; Hamzah, Ricda Nurhikmayanti; Safidni, Elvira; Rosmiati, Rosmiati; Hijrawati, Hijrawati; Ernawati, Ernawati; Rabuana, Susi (Barongko: Jurnal Ilmu Kesehatan, 2025)
Baby massage is one of the touch therapies that can meet the three basic needs, namely physical - biological needs, emotional - love needs, and stimulation needs, because in practice baby massage contains elements of touch in the form of affection, voice or speech, eye contact, movement, and massage. The purpose of the study was to stimulate the development and growth of babies in the Katimbang sub-district, Biringkanaya district. The research method used in this study was quantitative. using a pre-experiment in the one group pre-test-post-test design approach using a purposive sampling technique. The results of the study, the results of the statistical test using the Mann Whitney test obtained a p-value (0.009 <0.05). This states that Ha is accepted. The conclusion of the study shows that stimulation in the form of massage on babies has a positive impact on the development of babies that are carried out routinely, causing more optimal development.